Organisational Commitment of Contract Workers of Lumajang District Government After the Letter of the Minister of PAN and RB Number : B /185/M.SM.02.03/2022 - Hidayat, Zainul; Yatminiwati, Mimin; Ermawati, Emmy (International Journal of Accounting and Management Research, 2024)
This study aims to determine and analyse the effect of organisational commitment as the dependent variable of Lumajang District Government contract personnel after the Minister of PAN and RB Letter Number: B/185/M.SM.02.03/2022 concerning Personnel Status in the Agency Environment, Central and Regional Government. While the independent variables are organisational culture, transformational leadership and job satisfaction. This research method uses descriptive quantitative. The data used is primary data with a population of contract employees. The dependent variable in this study is organisational commitment with indicators. The independent variables in this study are the marketing mix consisting of organisational culture, and job satisfaction with each measuring instrument indicator and transformational leadership variables with measuring instrument indicators. Data analysis used multiple linear regression analysis. The results showed that partially organisational culture, transformational leadership, and job satisfaction had no effect on organisational commitment, and the results of testing all variables stated that organisational culture, transformational leadership and job satisfaction simultaneously had no effect on organisational commitment in contract employees within the Lumajang District Government